Influence of residual lime and plant growth regulator (naa) on the morphological and physiochemical traits of aromatic rice cv. kataribhog (SAARC Journal of Agriculture, 2017)
Abstract not availableSAARC J. Agri., 15(1): 189-197 (2017)